Money, credit, house prices and quantitative easing – the wavelet perspective from 1970 to 2016 - Ryczkowski, Maciej (Journal of Business Economics and Management, 2019)
This paper investigates the relationship between money/credit growth and house price inflation for a sample of twelve developed countries. The novel application of the continuous wavelet transform showed significant but time-varying linkages between these two variables. During quantitative easing in the United States and the United Kingdom, growth of respectively broad money and bank credit was leading house price inflation for the 2-8 years cycle. In contrast to this, the Bank of Japan and the European Central Bank either did not assign a separate role to house prices in their reaction functions or the two central banks were not capable to significantly increase house prices by extending money/credit during the business cycle. The significant co-movements of financial variables and house prices around booming episodes warn us that a new asset price boom might appear within the length of a business cycle as a consequence of overly expansionary monetary policy. In the euro area, the significant, long run, and close to a one-for-one link between growth of M3 and house price inflation is an argument for the monetary pillar of the European Central Bank. The present study contributes significantly to the literature by introducing a novel application of a continuous wavelet transform to study the housing prices in relation to money, credit and quantitative easing. The article uses a long-term dataset covering a period of almost half a century to analyse their varying relationship in the short-run to the long-run and from the historical perspective.